The impact of glidants on the rheological properties of active pharmaceutical ingredients: A study of conventional and alternative flow enhancers - Verbeek, Tom; De Man, Alexander; Van Snick, Bernd; Otava, Martin; Vervaet, Chris; Vanhoorne, Valérie (International journal of pharmaceutics, 2025)
Nowadays, most of the newly developed active pharmaceutical ingredients (APIs) consist of cohesive particles with a mean particle size of <100μm, a wide particle size distribution (PSD) and a tendency to agglomerate, therefore they are difficult to handle in continuous manufacturing (CM) lines. The current paper focuses on the impact of various glidants on the bulk properties of difficult-to-handle APIs. Three challenging powders were included: two extremely cohesive APIs (acetaminophen micronized (APAPμ) and metoprolol tartrate (MPT)) which previously have shown processing issues during different stages of the continuous direct compression (CDC)-line and a spray dried placebo (SD) powder containing hydroxypropylmethyl cellulose (HPMC), known for its sub-optimal flow with a high specific surface area (SSA) and low density. Four flow-enhancing excipients were used: a hydrophilic (Aerosil® 200) and hydrophobic (Aerosil® R972) fumed silica grade, a mesoporous silica grade (Syloid® 244FP), and a calcium phosphate excipient (TRI-CAFOS® 200-7). The APIs and binary API/glidant blends (varied between 0.5-2.75 w/w%) were characterized for their bulk properties relevant for CDC. The results indicated that optimizing different bulk parameters (e.g., density, flow, compressibility..) of an API required varying weight percentages of the glidant (e.g., different surface area coverage (SAC)) depending on the APIs. Moreover, even at similar SAC, the impact of the glidant on the bulk characteristic of the APIs depended on the glidant type properties. While nano-sized silicon dioxide were effective for improving the flowability of a powder, other glidants (mesoporous silica and tricalcium phosphate (TCP)) showed also promise as alternatives. Additionally, an excess of glidant, referred to as oversilication, negatively impacted some bulk parameters, but other characteristics were unaffected. Finally, to determine the appropriate concentration of the different classes of glidants, SAC calculations, an understanding of the glidant's working mechanism, and knowledge about the API's characteristics (i.e., morphology, compressibility, flowability, aeration, density, and wall friction) are required. This study confirmed the necessity of including various material characterization techniques to assess the impact of glidants on the bulk characteristics of APIs.
Keywords: fosforečnany vápenaté; pomocné látky; Bulk Drugs; Calcium Phosphates; Silicon Dioxide; paracetamol; Acetaminophen; Rheology; Particle Size; Hypromellose Derivatives; Rheological properties; prášky, zásypy, pudry; Powders; metoprolol; reologie; Excipients; Material characterization; nerozplněné léky; Continuous manufacturing; Drug Compounding; Metoprolol; velikost částic; deriváty hypromelózy; oxid křemičitý; příprava léků; Glidant; Flow enhancers